Needs Analysis for Developing a STEM Based E-LKPD Integrated with PjBL to Enhance Students’ Cognitive Learning Outcomes in Elementary Mathematics - Melisa; Agusdianita Neza; Susanta Agus; Ade Gusti Ningsih (Universitas Pendidikan Ganesha, 2026)
Socioeconomic changes and advances in information technology in the era of globalization require elementary school graduates to master 21st-century skills (7C). The Merdeka Curriculum encourages conceptual and contextual mathematics learning, including number patterns in Phase B. However, a gap remains between curriculum demands, digital media availability, and teachers’ pedagogical readiness. This study aims to analyze the needs for developing STEM based E-LKPD integrated with Project Based Learning (PjBL) to improve learning quality. This research uses a mixed method approach with a descriptive design. The research subjects consist of three mathematics teachers as interview informants and 33 teachers as survey respondents, with teaching module documents as supporting data sources. Data were collected through semi structured interviews, questionnaires, and document analysis, then analyzed using thematic analysis and descriptive statistics. The results show that learning is still dominated by conventional methods, with limited application of STEM and limited development of digital teaching materials. In addition, the learning modules are still weak in prerequisite competencies, integration of the Pancasila Student Profile, and differentiation strategies. The survey results show that most PjBL aspects fall into the moderate category, except for project scheduling, which is classified as strong. This study concludes that STEM PjBL based E-LKPD is needed to strengthen students’ conceptual, exploratory, and reflective skills as well as to support the implementation of the Pancasila Student Profile in mathematics learning. The implications of this study emphasize the importance of strengthening structured, contextual, and teacher needs based digital instructional design.